Competitiveness of a low specific power, low cut-out wind speed wind turbine in North and Central Europe towards 2050. (15th January 2022) - Swisher, Philip; Murcia Leon, Juan Pablo; Gea-Bermúdez, Juan; Koivisto, Matti; Madsen, Helge Aagaard; Münster, Marie
Abstract: This work is part of an ongoing study, creatively named the "LowWind Project" (Madsen et al., 2020), whose goal is to investigate at what price point a hypothetical 3.4 MW 100 W/m 2 low wind (LW) turbine with a hub height of 127.5 m, a rotor diameter of 208 m, and a cut-out wind speed of 13 m/s becomes competitive in Northern and Central Europe's energy system, as well as what impact the introduction of this technology has on the system. Similarly, the impact system flexibility has on LW investment is also analysed by limiting future transmission investment. Furthermore, this paper also analyses the amount of revenue this LW technology could generate compared to conventional turbines to further investigate the business case for this technology. The main finding here is that this LW technology begins to see investment at a 45% price increase over a conventional onshore wind turbine with an equal hub height (127.5 m) and a smaller rotor diameter (142 m vs 208 m). The addition of LW technology also leads to a reduction in transmission investment, and similarly, reductions in transmission capacity lead to further investment in LW technology. Lastly, it is shown that in the future Northern and Central European energy system, in wind dominated areas such as Denmark, this LW technology could generate revenues that are more than double that of conventional turbines (per MW), making the case that this technology could be a worthy endeavor. Highlights: Competitiveness of a 100 W/m 2 low wind turbine is investigated. Onshore wind turbine capacity factor and LCOE across Northern and Central Europe. Correlation between wind speed and electricity price in future European energy system. We must go beyond LCOE to analyse low specific power wind turbines. Lowering cut-out wind speed could lower wind turbine costs without hampering revenue.